Phylogenetic group, antibiotic resistance, virulence gene, and genetic diversity of Escherichia coli causing bloodstream infections in Iran - Hemati, Saeed; Halimi, Shahnaz; Jabalameli, Fereshteh; Emaneini, Mohammad; Beigverdi, Reza (Frontiers in Microbiology, 2024)
Escherichia coli is one of the most important pathogens causing bloodstream infections (BSIs) throughout the world. We sought to characterize the phylogroup classification, major human sequence types (STs), antimicrobial resistance, presence of selected antimicrobial resistance and virulence genes, and genetic diversity of E. coli isolated from patients with BSIs at the University Hospital in Iran. A total of 100 E. coli bloodstream isolates were collected between December 2020 and June 2022. This study used PCR to investigate phylogenetic groups (A, B1, B2, C, D, E, and F), four major STs (ST69, ST73, ST95, and ST131), antibiotic resistance genes (ARGs), virulence-associated genes (VAGs), and pathogenicity islands (PAIs). Antimicrobial susceptibility testing was done by disk diffusion method. Genetic diversity was analyzed by repetitive element sequence-based PCR (REP-PCR). The phylogenetic group B2 (32%) predominated, followed by phylogenetic group E (25%). ST131 (28%) was the most prevalent ST and the majority of these isolates (89.3%) were of serotype O25b. Most of E. coli isolates (75%) were categorized as multidrug resistant (MDR) with high rates of resistance (>55%) to ampicillin, trimethoprim-sulfamethoxazole, ciprofloxacin, cefazolin, and ceftriaxone. The most frequent ARGs were blaTEM (66%), sul1 (57%), and sul2 (51%). The most prevalent VAGs and PAIs were fimH (type 1 fimbriae adhesin; 85%), aer (iucC) (aerobactin; 79%), traT (serum resistance; 77%), iutA (aerobactin siderophore receptor; 69%), and PAI IV536 (75%), respectively. The highest rate of ARGs and VAGs was observed in the ST131 isolates. REP-PCR analysis showed high diversity among the studied isolates. The high prevalence of MDR septicemic E. coli with different types of ARGs, VAGs and genotypes is an extremely worrisome sign of BSIs treatment and poses a major threat for hospitalized patients. Active surveillance, stringent prescribing policies, increasing the awareness of ARGs among clinicians and re-defining the infection control measures are essential to curb the dissemination of these strains.